2018
DOI: 10.22159/ajpcr.2018.v11i12.28232
|View full text |Cite
|
Sign up to set email alerts
|

Applying Gata3 in Differentiating Urothelial Carcinoma From Prostatic Adenocarcinoma: An Immunohistochemical Study

Abstract: Objectives: Urothelial carcinoma and prostatic adenocarcinoma are the most common tumors of genitourinary system. Both tumors can demonstrate a broad morphology or present as poorly differentiated carcinoma occurring in urinary bladder or prostate or both organs that raise the suspicion of a locally extending or metastatic carcinoma from either organs. Accurate distinction between these tumors is mandatory because of different tumor biology and therapeutic protocols. In equivocal tumor morphology, the primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Results of the studies done by Abdullah et al (2018) and Liang et al (2014) were different as they reported that GATA-3 expression was not significantly associated with tumor stage. This incompatibility may be explained by the difference in sample size of the subgroups [18], [23]. In the present study, the tumor size had significant correlation with GATA3 expression (P value<0.001) i.e.…”
Section: A Statistically Significant Inverse Correlation Between Ck14 Expression and Gata3 Expression Wasmentioning
confidence: 86%
“…Results of the studies done by Abdullah et al (2018) and Liang et al (2014) were different as they reported that GATA-3 expression was not significantly associated with tumor stage. This incompatibility may be explained by the difference in sample size of the subgroups [18], [23]. In the present study, the tumor size had significant correlation with GATA3 expression (P value<0.001) i.e.…”
Section: A Statistically Significant Inverse Correlation Between Ck14 Expression and Gata3 Expression Wasmentioning
confidence: 86%